Rancang Bangun Alat Pendeteksi Gangguan Tegangan pada Gedung Elektro Politeknik Negeri Bengkalis Dengan SMS Berbasis Arduino - Beni Ade Saputra; Jefri Lianda (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2018)
Sudden outages or power failures caused by voltage drops or voltage loss in buildings often occur and are difficult to detect by PLN officers. This disorder requires information (phone, sms) from the campus Politeknik Bengkalis so that required a smart system. This study uses voltage sensors, data logger and GSM SIM800L to provide information if there is interference in the building. In the event of a power outage, this device is supplied by Power Bank as an energy reserve to provide the GSM SIM800L command to send an SMS command to the operator or PLN officer to provide information about the disturbance and record the old outage that will be calculated by the RTC and stored in SD CARD as a data collection officer of PLN.